Brachial Plexus Desmoid Tumor: Care for Functional Preservation - Andrew E. Liechty, BS; Yusha Liu, MD, PhD; Dennis S. Kao, MD (Plastic and Reconstructive Surgery, Global Open, 2020)
Summary:. Desmoid tumors are a rare, locally invasive, non-metastasizing tumor of mesenchymal origin. Most of such tumors occur sporadically, but some arise as part of germline adenomatous polyposis coli mutations. They tend to aggregate in the abdomen, thorax, extremities, and the head and neck region. They are challenging to treat, with a high rate of recurrence even if achieving negative margins. We present the case of an 18-year-old woman with a desmoid tumor involving her brachial plexus. A non-oncological resection was performed, with a focus on functional preservation. Residual disease is being treated with β-catenin inhibitor and monitored with serial MRI.